Imperial migrations : colonial communities and diaspora in the Portuguese world - Morier-Genoud, Éric; Cahen, Michel (Migration, diasporas and citizenship., 2012)
This volume explores the role and history of migration and diaspora within the Portuguese empire, investigating what role colonial communities and diaspora have had in shaping the Portuguese empire and its heritage. The book consists of twelve case studies which look at topics such as Portuguese migration to Africa, the Ismaili and the Swiss presence in Mozambique, the Goanese in East Africa, the Chinese in Brazil, and the history of the African presence in Portugal.